PENGARUH KONSENTRASI PUPUK ORGANIK CAIR NASA PADA PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L) - Army Dita Serdani; Palupi Puspitorini; Jeka Widiatmanta; Inggar Andhini Nindraningputri (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2023)
Green mustard plants are plants that are cultivated because they have high economic value and are needed by the community. However, there are problems in cultivation, one way to overcome them is by providing liquid organic fertilizer. NASA POC is a liquid organic fertilizer derived from agricultural and livestock waste which has a high macro and micro nutrient content. The aim of the research was to determine the best NASA POC concentration that increases the growth and yield of mustard greens (Brassica juncea L). The research used quantitative analysis designed in a 1 factor Randomized Block Design consisting of 6 levels and repeated 4 times. Observation variables were plant height, stem diameter and fresh weight of green mustard plants. The data was analyzed using variance. The results of this research were that the application of NASA POC of 10 ml/L was able to increase the height of green mustard plants by 21.53 cm, stem diameter by 14.40 cm, and fresh weight of mustard greens by 195.70 grams.